Perfil dos hormônios da tireoide em pacientes com câncer de mama em estado de menopausa - Conde, Sandro José Conde [UNESP]; Luvizotto, Renata de Azevedo Melo [UNESP]; Síbio, Maria Teresa [UNESP]; Saraiva, Patrícia Pinto; Brentani, Maria Mitzi; Nogueira, Célia Regina [UNESP] (FapUNIFESP (SciELO), 2012)
Objective: The aim of this study was to determine thyroid hormone (TH) profile in postmenopausal patients with breast cancer (BC). Subjects and methods: 12 CaM patients stages I or II, without interventions that could interfere with tumor progression were selected, as well as and a control group with 18 postmenopausal women without CaM. We measured serum anti-thyroperoxidase antibody (TPOAB), thyroid-stimulating hormone (TSH), free thyroxine (T4L), estradiol (E2), follicle-stimulating hormone (FSH), and luteinizing hormone (LH), before and after surgery, besides immunohistochemistry for estrogen (ER) and progesterone (PR) receptors. Results: Four patients with CaM showed changes in thyroid hormone profile: two had hyperthyroidism, one hypothyroidism, and one was positive for TPO-AB. All of them positive for ER and PR. TSH levels in breast cancer patients were not different from levels found in the control group (1.89 ± 1.56 vs. 2.86 ± 3.12 mIU/mL), but the levels of T4L in patients with CaM were statistically higher than those of the control group (1.83 ± 0.57 vs. 1.10 ± 0.20 ng/dL). Conclusion: These results reinforce the need for assessment of thyroid status in CaM patients, since in the absence of E2, changes in clinical HTs can act in E2-controlled processes. © ABE&M todos os direitos reservados.
Thyroid hormone profile in breast cancer patients in postmenopause
Keywords: Breast neoplasms; Hyperthyroidism; Postmenopause; Thyroid hormones